Development of a shape-memory-alloy micromanipulator based on integrated bimorph microactuators - AbuZaiter, Alaa (Elsevier Ltd, 2016)
This paper reports a novel structure of a shape-memory-alloy (SMA) micromanipulator with gripping mechanism. A featured integration of multiple SMA bimorph microactuators has been utilized to form a micromanipulator with three degrees of freedom. The design consists of two links (SMA sheets) and a gripper at the end of the second joint. The overall dimensions of the micromanipulator are 33 mm × 9 mm × 3 mm. The displacement of each actuator is controlled by a heating circuit that generates a pulse-width modulation signal. Theoretical modeling of SMA actuators is studied and verified with simulation. The SMA micromanipulator is able to move in the x- and y-axis by 7.1 mm and 5.2 mm, respectively, resulting in a maximum displacement of 8.9 mm. The micro-gripper has a maximum opening gap between its fingers of 1.15 mm. The micromanipulator has a temporal response of 7.5 s and 9 s for its x- and y-axis. The maximum actuation force generated by the x- and y-axis was around 100 mN and 130 mN, respectively. The developed micromanipulator has been successfully used to move a small object.